Bailando en silencio : escenas de una niñez puertorriqueña - Cofer, Judith Ortiz, 1952- (Recovering the U.S. Hispanic Literary Heritage Project publication., 1997)
A collection of writings by the poet, novelist, and essayist recalling her childhood spent shuttling between the land of her birth and the family's home in New Jersey.